Inflation: Pragmatics of money and inflationary sensoria - Federico Neiburg (economic sociology. perspectives and conversations, 2023)
Inflation's recent transformation into a first-order global issue provides us with an occasion to update how the social sciences view it. The effects of the Covid-19 pandemic, the war in Ukraine, and the environmental crisis have generated a cascading series of phenomena, including emergency injections of liquidity to maintain minimum spending power for poor people and to ensure companies' survival, supply chain interruptions, and a general spike in the prices of basic goods, such as food, water, and energy.
Keywords: 300